Influencing Factors Financial Statement Fraud In terms of Fraud Hexagon - Lexia Ifani; Erna Puspita; Andy Kurniawan (Program Studi Akuntansi Universitas Islam Lamongan, 2024)
This research aims to identify the influence of the fraud hexagon which is proxied by external pressure, change of auditor, ineffective supervision, change of board of directors, CEO image frequency, cooperation projects with the government on financial statement fraud. Banking and financial sector companies listed on the Bursa Efek Indonesia (BEI) in 2020-2022 were used as the population in this research. In this research, the results showed that the independent variables consisting of external pressure, change of auditor, ineffective monitoring, change of board of directors, CEO image frequency and cooperation with the government had a simultaneous effect on the dependent variable fin|anci|al st|atement fr|aud. P|arti|ally, the v|ari|ables th|at h|ave |a signific|ant influence on fin|anci|al st|atement fr|aud |are extern|al pressure, ineffective monitoring, |and CEO image frequency. Meanwhile, the variables change of auditor, change of board of directors, |and cooper|ation with the government do not h|ave |a signific|ant effect on fin|anci|al st|atement fr|aud.